Analisis Usaha Wanita Pengrajin Agroindustri Kerupuk Ubi di Kecamatan Kampar Kabupaten Kampar - Susy Edwina; Diana Rabesdini; Rina Andriana (Universitas Riau, 2007)
This research analyzed the women income and economic efficiency of cassava chip agroindustry in district of Kampar. Survey method used for this research was purposive sampling. Primary data was collected from 22 respondents, while secondary data was obtained from related agencies, both consisted of qualitative and quantitative data. The cassava chip agroindustry has diversified its products. The average earning of respondents was Rp. 1.093.768,45 per month. Based on this matters, this business is efficient and competent to be developed. Key words: agroindustry, cassava chip, efficiency